Evaluasi Kinerja Guru; Manajemen Evaluasi Peningkatan Profesionalitas Guru - Muhammad Sholahudin (INSTITUT AGAMA ISLAM BANI FATTAH (IAIBAFA), 2013)
eacher performance evaluation program conducted adhering to the principles of management, which includes four components, namely planning, organizing, implementing and monitoring of teacher performance evaluation program. Clearly is: (1) in the planning stages, has compiled the purpose, format and procedures for teacher performance evaluation program. The objective is to evaluate the applied profession, improving overall performance and overall teacher mapping, (2) the organizing stage, the organizational structure of teacher performance evaluation program is a form of organizational structure where the line is comprised of the Chairman of the foundation, the school principal, coordinator of field curriculum, student field coordinator, and coordinator of facilities and infrastructure, thus existing division of tasks for each coordinator to avoid overlapping responsibilities, (3) the stage of implementation of teacher performance evaluation conducted simultaneously to all employees both teachers and employees every year In order for the evaluation of teacher performance can work well, principals and teachers disseminate to all employees regarding time, methods, and procedures used in the evaluation process. (4) Under the supervision of teacher performance program annually after evaluation program was conducted to determine the lack of improvement in the future.